The equivalent expression is:
[tex](3a +b)(2a-4b) = 6a^2 -10ab -4b^2[/tex]
Solution:
Given that,
We have to find the equivalent expression
Given expression is:
[tex](3a +b)(2a-4b)[/tex]
Multiply each term in first parenthesis with each term in second parenthesis
[tex]\rightarrow (3a +b)(2a-4b) = (3a \times 2a) -(3a \times 4b) + (b \times 2a) -(b \times 4b)\\\\Simplify\ the\ above\\\\\rightarrow (3a +b)(2a-4b) = 6a^2 -12ab + 2ab -4b^2\\\\Combine\ the\ like\ terms\\\\\rightarrow (3a +b)(2a-4b) = 6a^2 -10ab -4b^2[/tex]
Thus the equivalent expression is found